Case Report: A case of subacute combined degeneration of the spinal cord associated with chronic atrophic gastritis, macrocytic anemia, and positive anti-sulfatide IgM and IgG antibodies - Zhuang, Shun-Zhi; Li, Cai-ming; Kong, Ling-en; Lin, Bi-hua; Zhu, Cai-ling (Frontiers in Immunology, 2025)
BackgroundAnti-sulfatide antibodies are autoantibodies that are associated with various neurological disorders. They have been identified in several conditions including Guillain–Barré syndrome, multiple sclerosis, and chronic inflammatory demyelinating polyneuropathy. Subacute combined degeneration of the spinal cord is mainly caused by vitamin B12 deficiency. Chronic atrophic gastritis is a complex condition characterized by atrophy and inflammation of the gastric mucosa. To date, there have been no reported cases of patients with subacute combined degeneration of the spinal cord co-occurring with chronic atrophic gastritis and positive anti-sulfatide antibodies.Case presentationA 58-year-old male patient presented with symmetrical progressive numbness of his limbs. Although he did not experience gait instability, he had difficulty performing fine motor tasks in his upper limbs. We reviewed the patient’s medical history and analyzed the results of his blood tests, imaging studies, and gastroscopic. The patient met the criteria for subacute combined degeneration of the spinal cord, chronic atrophic gastritis, macrocytic anemia, and anti-sulfatide antibody positivity. His symptoms improved after treatment.ConclusionThis is the first report on the coexistence of positive anti-sulfatide antibodies and subacute combined degeneration of the spinal cord, including chronic atrophic gastritis and macrocytic anemia, which will enhance our understanding of the relationships between these conditions.